OS INFORTÚNIOS DE DUAS MULHERES DESCENDENTES DE IMIGRANTES EM MALLET, PARANÁ: VIOLÊNCIA EM PROCESSOS-CRIME DA DÉCADA DE 1960 - MOURA, STEFANY ARGEANE ROLIM DE (2022)
This work aims to study/analyze the discourses present in five criminal proceedings from the 1960s, which involve subjects from the same poor family in the city of Mallet, Paraná. One of the criminal proceedings investigated the practice of infanticide attributed to two women of this family, another three concern violent practices aimed at this group, and the last criminal proceeding investigated an attempt to set fire to their residence. It is intended to study, from these sources, the narratives developed and intermediated by police authorities and the Judiciary, in addition to their possible developments. The analysis of the sources will be based on concepts proposed by Michel de Certeau and by Michel Foucault, understanding these historical vestiges as the place of the event of words and power relations.